2022
DOI: 10.1088/1755-1315/969/1/012050
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the pH of mosquito repellent from citronella using response surface methodology

Abstract: Citronella is a source of essential oil obtained from steam distillation. The production of citronella oil is quite high; therefore, it can be applied in various fields. One of its applications is as an active substance in mosquito repellent creams. The citronella oil used in this study contained 11.59% citronellol content at a retention time of 16.544 minutes and citronellol content of 14.78% at a retention time of 27.165 minutes using the Gas Chromatography Mass Spectrometry method. In the manufacture of mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This result agrees with Handayani et al, which found that the pH value will decrease along with the increase in cetyl alcohol content. 30 The five formulas proved stable because storage under ambient conditions and freeze-thaw cycles revealed no significant pH changes.…”
Section: Resultsmentioning
confidence: 93%
“…This result agrees with Handayani et al, which found that the pH value will decrease along with the increase in cetyl alcohol content. 30 The five formulas proved stable because storage under ambient conditions and freeze-thaw cycles revealed no significant pH changes.…”
Section: Resultsmentioning
confidence: 93%